Furostanol Saponins from the Bulbs of Welsh Onion, Allium fistulosum L. - Zolfaghari, Behzad; Yazdiniapour, Zeinab; Sadeghi, Masoud; Troiano, Raffaele; Lanzotti, Virginia (Planta Medica, 2016)
An extensive phytochemical analysis of the polar extracts from bulbs of Welsh onion Allium fistulosum L. led to the isolation of nine saponins, four of them, named fistulosaponins G (1a/1b), H (2), I (3a/3b), and J (4), have never been reported previously. Fistulosaponins G and I were isolated as a couple of isomers in equilibrium. On the basis of 2D NMR and mass spectrometry data, the structure of the novel compounds were elucidated as (25R)-26-[(β-D-glucopyranosyl)oxy]-3β,22β-dihydroxyfurost-5-en-1β-yl O-α-L-rhamnopyranosyl-(1 → 4)-O-α-L-rhamnopyranosyl-(1 → 4)-β-D-glucopyranoside (1a) with its 22α epimer (1b), (25R)-26-[(β-D-glucopyranosyl)oxy]-3β-hydroxyfurost-5,20-dien-1β-yl O-α-L-rhamnopyranosyl-(1 → 4)-O-α-L-rhamnopyranosyl-(1 → 4)-β-D-glucopyranoside (2), (25R)-26-[(β-D-glucopyranosyl)oxy]-3β,22β-dihydroxyfurost-5-en-1β-yl O-α-L-rhamnopyranosyl-(1 → 4)-β-D-glucopyranoside (3a) with its 22α epimer (3b), and (25R)-26-[(β-D-glucopyranosyl)oxy]-3β-hydroxyfurost-5,20-dien-1β-yl O-α-L-rhamnopyranosyl-(1 → 4)-β-D-glucopyranoside (4). This is the first report of furostanol saponins in A. fistulosum bulbs. In addition, data on the antibacterial tests of the isolated saponins against Escherichia coli and Enterococcus faecalis are reported.
Keywords: Welsh onion; Allium fistulosum L.; Amaryllidaceae; furostanol saponins; fistulosaponins; NMR spectroscopy; antibacterial tests